2010
DOI: 10.5694/j.1326-5377.2010.tb04108.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of red‐bellied black snake ( Pseudechis porphyriacus ) envenoming and correlation with venom concentrations: Australian Snakebite Project (ASP‐11)

Abstract: Objective: To describe the clinical features and laboratory findings in patients with definite red‐bellied black snake (RBBS; Pseudechis porphyriacus) bites, including correlation with results of venom assays. Design, patients and setting: Prospective cohort study of patients with definite RBBS bites, recruited to the Australian Snakebite Project from January 2002 to June 2010. Main outcome measures: Clinical and laboratory features of envenoming; peak venom concentrations and antivenom treatment. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 17 publications
(19 reference statements)
7
61
0
Order By: Relevance
“…It also explains, in part, the reason for the predominance of upper limb bites, when compared to other studies of Australian snakes [37]. The study supports the fact that death adder bites from snakes in the wild are rare.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It also explains, in part, the reason for the predominance of upper limb bites, when compared to other studies of Australian snakes [37]. The study supports the fact that death adder bites from snakes in the wild are rare.…”
Section: Discussionsupporting
confidence: 83%
“…An anticoagulant type coagulopathy was seen in two patients, an effect that has not been described in Australian death adder bites before. This is similar to the coagulopathy seen in Australian black snake bites with an elevation of the aPTT [37] and although a useful marker of envenoming is unlikely to be clinically significant. Normal fibrinogen levels confirm that it is not a consumption coagulopathy.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, cases of black snake ( Pseudechis porphyriacus ) were included from the Australian snakebite project19. The design of the Australian snakebite project has previously been described in detail and approval has been obtained from the Hunter New England Area Health Human Research Ethics Committee and nineteen other Human Research and Ethics Committees covering all institutions involved around Australia1920. Informed consent was obtained from all patients and the experiments were undertaken in accordance with the National Health and Medical Research Council guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Serum samples were tested with venom specific enzyme immunoassay (EIA) for Russell's viper venom and hump-nosed pit viper venom for Sri Lankan cases, and black snake venom for Australian cases, to confirm envenomation319. Clotting studies on citrate samples and clinical data were used to confirm systemic envenoming32122.…”
Section: Methodsmentioning
confidence: 99%
“…However, a study of bites by the Australian red-bellied black snake, Pseudechis porphyriacus , demonstrated no correlation between peak venom antigen concentration and clinical severity of envenoming 34. We identified several patients bitten by N. kaouthia with minimal signs of either local or systemic envenoming.…”
Section: Discussionmentioning
confidence: 76%